How football team composition constrains emergent individual and collective tactical behaviours: Effects of player roles in creating different landscapes for shared affordances in small-sided and conditioned games - Laakso, T.; Davids, K.; Luhtanen, P.; Liukkonen, J.; Travassos, B. (International Journal of Sports Science & Coaching, 2022)
The aim of the present study was to examine how team composition of players with different roles constrains individual and collective tactical behaviours, and ball possession effectiveness, during competitive 3 vs 3 small-sided and conditioned games (SSCGs) in youth soccer players. Fifteen male players (under 15 yrs, mean age 13.2 ± 1.03 years, mean years of practice: 4.2 ± 1.10 years) from the same club participated in this study. For analysis purposes, on advice from the coaching staff, participants were categorised according to their main team performance role, resulting in sub-samples of 5 defenders (centre-backs = 2 and full- backs = 3), 7 midfielders (central midfielders = 3 and wide midfielders = 4) and 3 attackers (forwards). In order to assess participant tactical behaviours, a notational analysis system was created with four categories: i) team behaviours, ii) individual players offensive actions, iii) individual players defensive actions, and iv), ball possession effectiveness. Analysis of players offensive actions revealed that the team composed only of midfielders revealed a higher frequency of diagonal and vertical passes in relation to the attackers team. In offensive individual actions, the attackers team revealed more dribbles in relation to the teams of defenders and midfielders. Analysis of ball possession effectiveness revealed that the team of defenders achieved higher values of shots on goal compared to the team of midfielders. These findings exemplified how playing role constrains the emergence of different collective behaviours and individual actions in 3 vs 3 SSCGs.